Exploitation et commercialisation de la pourpre dans l'Empire romain - Macheboeuf, Christine (DAN@, 2022)
Sea Purple dye, extracted from the shells usually called Bolinus brandaris, Hexaplex trunculus and Purpura haemastoma was exploited from the Bronze Age till the middle of the XVth century AD. Yet, its production was indeniably the most intensive from the second to the fifth century AD. Indeed, the Romans were strongly attracted by this animal dye which was originally a symbol of power. Consequently, the elite spent huge amount of money to wear purple clothes of which the ancient authors continually praised the beauty. This essay about the exploitation and the selling of purple in the Roman Empire follows the manufacturing process of its production, from fishing to the selling of finished goods. That is how the murex fishing are mentioned as well as the different means to preserve them alive and the treatments they received to reveal their dyeing juice. The manufacture of the dye is detailed step by step and the ancient writing enlightened by the constant efforts of experimental archeology. A working hypothesis about the causes of the color differences of the dyeing juice of the Murex depending on their geographic location is brought about and leads to study the ars purpuraria as well as the numerous colors created by the dyers. It is a thorough study focused on the shore workshops which are the main spots producing purple, it also displays a detailed reconstruction. The status of men, from the fishermen to the dyers who have worked in these workshops are exposed and the management of the imperial producer worshops is broached. Lasly, the conclusions of our experiments on the preservation allow us to evoke the possibility to dye in purple inland. It is the opportunity to study the actors of this production as well as the different professions and places connected to the selling of purple.